Kedudukan Anak Perempuan dalam Pembagian Harta Warisan menurut Hukum Islam (Studi Kasus Putusan Pengadilan Agama Medan No. 40/Pdt.G/2017/PA.Mdn) - Saragih, Emy Eliamega; Mustamam, Mustamam; Mukidi, Mukidi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The problem in this study, regarding the position of girls in the distribution of inheritance law according to Islam, concerning inheritance rights of siblings of fathers who leave a daughter in the perspective of Islamic law and on the basis of judges' consideration in determining the determination of heirs in the decision of case register No. 40/Pdt.G/2017/PA.Mdn. This research is a normative juridical approach with a case approach by analyzing Decision No. 40/Pdt.G/2017/PA. Mdn). The data source of this research is secondary data obtained from the results of library research. Data analysis used in this study is qualitative data analysis. Based on the research results obtained, that the position of girls in the distribution of inheritance law according to Islam is the same as that of boys, namely both have the right to inherit the inheritance of their parents or relatives. It's just that, the male portion is bigger than the female part, which is two parts of the two girls. The inheritance rights of the father's siblings who leave a daughter in the perspective of Islamic law are based on bi ghairihi asabah, because they inherit from men and women together. The basis of the judge's consideration in determining the determination of the heir in the decision of case register No. 40 / Pdt.G/2017/PA.Mdn, is Article 174 paragraph (2) KHI and Al-Quran Letter of Examination verse 176. The panel of judges has mistakenly interpreted the substance of the Examination paragraph 176 and also interpreted the provisions of Article 174 paragraph (2) KHI.